Welfare resilience at the onset of the COVID-19 pandemic in a selection of European countries: Impact on public finance and household incomes - Olga Cantó-Sánchez; Francesco Figari; Carlo Fiorio; Sarah Kuypers; Sarah Marchal; Marina Romaguera de la Cruz; Iva Valentinova Tasseva; Gerlinde Verbist (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2021)
This paper assesses the impact on household incomes of the COVID-19 pandemic and governments' policy responses in April 2020 in four large and severely hit European countries: Belgium, Italy, Spain and the UK. We provide comparative evidence on the level of relative and absolute welfare resilience at the onset of the pandemic, by creating counterfactual scenarios using the European-wide tax-benefit model EUROMOD combined with COVID-related household surveys and timely labour market data. We find that income poverty increases in allcountries due to the pandemic while inequality remains broadly the same. Differences in the impact of policies across countries arise from four main sources: the asymmetric dimension of the shock by country, the different protection offered by each tax-benefit system, the diverse design of discretionary measures and the differences in the household level circumstances and living arrangements of individuals at risk of income loss in each country.
Keywords: 330; Poverty; Labour Market; Households; Income Dynamics; Microsimulation; Health; Covid-19; Taxation; Welfare Benefits; Economics; Public Policy